Effect of crystallographic orientation on the hardness of polycrystalline materials AA7075. (May 2019) - Zhao, Man; Ji, Xia; Li, Beizhi; Liang, Steven Y
As one of the most important properties of materials, micro-hardness is influenced by material microstructure significantly. The reported data show that the micro-hardness of materials varies with the variation of crystallographic orientation. This paper presents an analytical model to quantify the effect of crystallographic orientation on micro-hardness by analyzing the mechanical behavior in the test of Vickers hardness. The plastic deformation occurs under the micro-indentation with the flow stress affected significantly by crystallographic orientation of material. This paper develops a Taylor factor model to quantify the effect of crystallographic orientation on the flow stress of polycrystalline materials, by examining the number and the style of activated slip systems. Considering the linear relationship between the flow stress and Vickers hardness, the effect of crystallographic orientation on the Vickers hardness is established. To verify the Taylor factor model, compression tests and Vickers hardness tests were conducted. The result shows that the predictions coincided with the experimental data, which suggests that the model considering the variation of crystallographic orientation is accurate and the Taylor factor model is reasonable. To analyze the sensitivity of flow stress and Vickers hardness to CO, this paper also predicted flow stress and hardness using models without considering the variability of Taylor factor and the athernal stress. The three predictions were compared with the experimental data, and the results proved that the model considering the variability Taylor factor improves flow stress and accuracy of hardness models.